1990
DOI: 10.1002/mrd.1080250306
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the human sperm acrosome reaction using concanavalin a lectin

Abstract: A method for assessment of the human sperm acrosome reaction is reported using fluorescein isothiocyanate (FITC)-conjugated Concanavalin A (ConA). The technique involved labelling prefixed spermatozoa, where only those spermatozoa that showed a complete loss of the acrosome bound FITC-ConA to the acrosomal region. Competitive sugar binding studies demonstrated that binding of ConA lectin to the acrosomal area of human spermatozoa was inhibited in the presence of 0.2 M D-mannose. Staining with the supravital st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 21 publications
1
39
0
2
Order By: Relevance
“…In UV light microscopy the incidence of human spermatozoa with a highly fluorescent anterior region of the sperm head increases by about 3.5-fold between 1 and 5 h of capacitation [6]. Electron microscopy studies have revealed gold-conjugated Con-A bound specifically to the surface of the inner acrosomal membrane of acrosome-reacted spermatozoa after 1 h of incubation with calcium ionophore A-23 187 [9]. This is in accordance with our results, since at 30 min of incubation a weak label increased predominantly in the inner acrosome membrane after an hour of incubation with the ionophore.…”
Section: Discussionmentioning
confidence: 99%
“…In UV light microscopy the incidence of human spermatozoa with a highly fluorescent anterior region of the sperm head increases by about 3.5-fold between 1 and 5 h of capacitation [6]. Electron microscopy studies have revealed gold-conjugated Con-A bound specifically to the surface of the inner acrosomal membrane of acrosome-reacted spermatozoa after 1 h of incubation with calcium ionophore A-23 187 [9]. This is in accordance with our results, since at 30 min of incubation a weak label increased predominantly in the inner acrosome membrane after an hour of incubation with the ionophore.…”
Section: Discussionmentioning
confidence: 99%
“…This preliminary binding will boost-up the acrosome reaction which further releases acrosomal enzymes and its activation. This in association with the obtained hyper activated motility will trigger the sperm to penetrate zona pellucida (Holden et al, 1990). Premature acrosome reactions figure the sperm infertile, and therefore, assessment of acrosome integrity is very important for fertilization to occur.…”
Section: Advances In Animal and Veterinary Sciences August 2014 | Volmentioning
confidence: 99%
“…For human sperm concanavalin A lectins (ConA) is used as well (Holden et al, 1990). The PNA labelling is specific for the outer acrosomal membrane and it binds to -galactose moieties.…”
Section: Acrosomal Membrane Integritymentioning
confidence: 99%